The Impact of Interactive Marketing on Achieving Strategic Ambidexterity: (An Analytical Study of the Opinions of a Sample of Telecommunications Companies in Erbil Governorate) - خطاب محمد, هازة; غريب محمد, مه ريوان (The Scientific Journal of Cihan University– Sulaimaniya, 2023)
Objective: This research aimed to determine the impact of interactive marketing for telecom companies, represented by its dimensions (trust, interaction, service quality, response to customer complaints) on the dimensions of strategic ingenuity represented by (strategy exploring opportunities, strategy exploiting opportunities, structural ingenuity). General framework: The general framework of the study represents the problem of the study, which identified by raising several questions about the nature of the relationship, the impact, and the variance between the independent variable (interactive marketing) and the dependent variable (strategic ingenuity). All hypotheses were subjected to multiple tests, and the study used a questionnaire as a means to obtain data. Study Methodology: The study followed the descriptive analytical approach, where the main and sub-variables were described, as well as to analyze the impact between the variables. The study population represented the telecommunications companies in the province of Erbil, which numbered (4) companies. As for the responding individuals, their number reached (91) cadres of the sales department and for the services of the study sample. Hypotheses were tested by applying statistical methods using the computer program (SPSS V.22). The value of the study: The study reached a set of main conclusions, including the results of the correlation analysis revealed the existence of positive and high-level moral relationships between interactive marketing and strategic ingenuity at the macro and micro levels, and this confirms the benefit of the researched organizations from identifying interactive marketing and its contribution to strategic ingenuity. In addition, there is a positive and significant effect of the interactive marketing variable on the strategic ingenuity variable, according to what was revealed by the analysis indicators at the overall level, as well as the regression results indicated the presence of an effect for each of the dimensions of interactive marketing (trust, interaction, service quality, response to customer complaints) respectively contributed to this effect. Conclusions and Suggestions: The research reached a set of conclusions, the most prominent of which is the existence of a significant and positive correlation between and at a good level between interactive marketing and strategic ingenuity according to the macro and micro levels, which indicates that the greater the use of the surveyed communication companies, the more interactive marketing this leads to enhancing their method of applying Strategic ingenuity. In addition to the presence of a positive effect of the interactive marketing variable on strategic ingenuity, according to the results of the statistical analysis according to the total level, while the regression results revealed that there is an effect for each dimension of interactive marketing, respectively, in achieving strategic ingenuity.